Process Mining to Improve the Development of the Course Syllabus - Wisudiawan, Gede Agung Ary (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
This paper focused on how to improve the development of course syllabus using process mining. Course syllabus developers need more input when making improvements. In this paper, the improvement of course syllabus development is based on enriching the input process of course syllabus development. The input based on the facts from student activities when student use LMS. LMS has an event log that keeps logs of student activities while using the LMS. The event log will be mined using a process mining, the algorithm used in this process mining is heuristic algorithm. Process mining is proven to be able to enrich the input in the development of course syllabus. The first finding is that there are two topics that are carried out simultaneously. The topic is the topic 7th and 8th as well as the 12th and 13th. The second finding is that there are jumping week that can be seen at the 2nd topic, directly to the 6th topic and at the 9th topic, continued to the 11th topic. These findings can be used to enrich input during development of the course syllabus. Regarding the evaluation of the model process from student learning activities, database modeling for one semester at the LMS that was formed is as follows: the fitness value is 99%, the generalization value is 99%, and the precision value is 45%.